Efektivitas Pemberian Oksigen Posisi Semi Fowler Dan Fowler Terhadap Perubahan Saturasi Pada Pasien Asma Bronkial Persisten Ringan - Syamsul Firdaus; Misbachul Munirul Ehwan; Agus Rachmadi (Poltekkes Kemenkes Jakarta III, 2019)
Mild persistent bronchial asthma is a chronic inflammatory airway that cause the low oxygen saturation value (91-95%). Administering oxygen therapy, setting the position of the semi fowler and fowler can reduce the risk of a decreased chest configuration. This research aims to assess the difference of effectiveness of administering oxygen at semi fowler with fowler position to the saturation changes in mild persistent bronchial asthma patients in Ratu Zalecha Martapura Hospital. This research method is quasy Experiment. The population research are all patients who experience mild persistent bronchial asthma attack, the sample of this research are 20 respondents with purposive sampling technique and analyzed with independent T test. The results is at semi fowler position the average of oxygen saturation before the treatment is 93.10%, after administering oxygen therapy with semi fowler position the average saturation is 98.00%. At the fowler position the average of oxygen saturation before the treatment is 92.60%, after administering oxygen therapy with fowler position the average saturation is 98.00%. The independent T-test result showed no difference of effectiveness of administering oxygen at semi fowler with fowler position to the saturation changes in mild persistent bronchial asthma patients,so teh patients can be given both positions.